Sejarah dan Tranformasi Politik Turki: Pergulatan Sekularisme dan Islamisme - Adib Khairil Musthafa; Hanik Purwati (Jurnal Tamaddun, 2022)
Abstract: It is known that in its historical record, Turkey was the first "Islamic" country to boldly adopt secularism, however, Islamism of course cannot be separated from the life of Turkish society. Not only because of the history of the great empire of Islam in the past: the Ottoman dynasty, but Islamic religious values have taken root in the life of the Turkish people. The recent rise of Turkish Islamists must be seen as historical implications, the climate in Turkey's political tradition which often clashes two ideological groups such as Islamism and Secularism, of course, cannot be separated from the long journey of this country, Turkey's political transformation occurs with various dynamics surrounding it both in the name of democracy. but the practice of political pragmatism often brings Turkey to identity politics tensions. This article aims to describe the history of Islam and Turkish politics, how its political transformation, the birth of the Turkish republic, the transformation of its political system and culture to democratization efforts and the revival of political Islam groups in Turkey.